The Protective Role of Single Bulb Garlic Towards Vascular Cell Adhesion Molecules-1 (VCAM-1) on Mice With High-Fat Diet - Chasanah, Isfatun; Gofur, Abdul; Lestari, Sri Rahayu (Jurnal Akademika Kimia, 2019)
Atherosclerosis is initiated by inflammatory response characterized by the accumulation of lipids in the arteries, causing blockage of blood vessels. The excessive of Low-Density Lipoprotein (LDL) in the blood is a major factor in endothelial dysfunction and results in an inflammatory process. The inflammatory process in atherosclerosis is due to the expression of adhesion molecules Vascular Cell Adhesion Molecules-1 (VCAM-1). This research aims to evaluate the effect of single bulb garlic oil extract (SGBOE) against VCAM-1 expression high-fat diet mice. Male mice strain Balb/C were acclimatized for one week. Mice were divided into 6 groups (n=5): normal, high-fat diet (HFD), HFD + simvastatin, and HFD + SBGOE 12.5, 25, and 50 mg/kg BW respectively. HFD was given for 45 days. Single garlic extract was given for four weeks orally. The aortic VCAM-1 expression was assayed using the Immunohistochemical-Flouresence (IHK-F) method. The result of One-Way ANOVA showed that the treatment influenced significantly (p<0.05). The foam cells increase in the high-fat diet group compared than normal mice. Dose 12,5 mg/kg BW reduces VCAM-1 expression near the normal group. Allicin and S-allyl cysteine (SAC) compounds in single bulb garlic are antioxidant compounds that act to prevent oxidative stress and prevention mechanisms against lipoprotein modification.